How To Be a Better Scientist. By Andrew C. Johnson and John P. Sumpter. Taylor and Francis, 2018. Pp. 248. Price GBP 15.19 ISBN 9781138731295 (paperback), GBP 76.00 ISBN 9781138731219 (hardback), GBP 12.34 ISBN 9781315189079 (ebook). Issue 3 (27th May 2020) - Helliwell, John R.
Abstract : Book review. Abstract : Book review.